Penerapan Branding Produk Sebagai Strategi Digital Marketing di KWT Ngesti Rahayu Melalui Literasi Ekonomi - Budiono, Desi; Wibawa, Fajri Arif; Maretta, Gres; Nisa, Fadinda Khoirun; Kumara, Latif (SINAR SANG SURYA, 2025)
The Ngesti Rahayu Women Farmers Group (KWT) is a group of women farmers located in Ngesti Rahayu village, Punggur sub-district, Central Lampung Regency. KWT Ngesti Rahayu has human resource protection and agricultural products such as herbal medicine products made from natural herbal ingredients/organic medicinal plants, cassava cracker products, rengginang products and there are also products made from cassava. The problem faced by partners lies in their competence/skills in introducing products to the general public. There is no assistance in branding products produced at KWT. So it is necessary to make efforts to improve the results of the KWT product. To increase economic literacy, the service team is trying to provide training on KWT Ngesti Rahayu product branding as a digital marketing strategy. The method used in this activity is to deliver the material interactively and practically. To measure material achievement, an evaluation is carried out at the end of the activity. The instruments used were multiple choice questions and a Likert scale. The results of the activity showed participants' awareness of branding challenges through an economic literacy review of participants' knowledge and skills.